Who drives change? Comparing the evolution of domestic climate governance in India and South Africa - Never, Babette (2012)
Abstract: This article compares and contrasts the nature and scope of change in the domestic climate governance of India and South Africa between 2007 and 2010. It identifies the actors and networks driving these change processes by applying the concepts of “communities of practice” and a simple, resource exchange–based network. Small communities of practice promoting collective learning, trust, and identity building capture the trends and actor relations well for the South African case. More simple, business-driven networks could be identified in India. Using survey and interview data, this article finds that both countries have generally not undergone a structural, transformative change, yet that includes the collective learning of new norms and values. Differences exist for more specific parts of climate governance. The number of participating actors, the character of the scientific landscape, and the centrality of a governmental actor with a certain knowledge and attitude within a networ